Report on the 16th National Scientific Conference in the “Humanistic Ecology” Series: “Man for the City – the City for Man” (Warsaw, 26 October 2022) - Ryszard F. Sadowski (Studia Ecologiae et Bioethicae)
The abstract is not available for the report.